A Review of Landfill Microbiology and Ecology: A Call for Modernization With ‘Next Generation’ Technology - Meyer-Dombard, D’Arcy R.; Bogner, Jean E.; Malas, Judy (Frontiers in Microbiology, 2020)
Engineered and monitored sanitary landfills have been widespread in the U.S. since the passage of the Clean Water Act (1972) with additional controls under RCRA Subtitle D (1991) and the Clean Air Act Amendments (1996). Concurrently, many common perceptions regarding landfill biogeochemical and microbiological processes and estimated rates of gas production also date from 2-4 decades ago. Herein we summarize the recent application of modern microbiological tools as well as recent metadata analysis using California, USEPA and international data to outline an evolving view of landfill biogeochemical/microbiological processes and rates. We focus on U.S. landfills because these are uniformly subject to stringent national and state requirements for design, operations, monitoring, and reporting. From a microbiological perspective, because anoxic conditions and methanogenesis are rapidly established after daily burial of waste and application of cover soil, the >1000 U.S. landfills with thicknesses up to >100m form a large ubiquitous group of dispersed ‘dark’ ecosystems dominated by anaerobic microbial decomposition pathways for food, garden waste, and paper substrates. We review past findings of landfill ecosystem processes, and reflect on the potential impact that application of modern sequencing technologies (e.g., high throughput platforms) could have on this area of research. Moreover, due to the ever evolving composition of landfilled waste reflecting transient societal practices, we also consider unusual microbial processes known or suspected to occur in landfill settings, and posit areas of research that will be needed in coming decades. With growing concerns about greenhouse gas emissions and controls, the increase of chemicals of emerging concern in the waste stream, and the potential resource that waste streams represent, application of modernized molecular and microbiological methods to landfill ecosystem research is of paramount importance